2013
DOI: 10.1177/1464884913496498
|View full text |Cite
|
Sign up to set email alerts
|

Media construction of a school shooting as a social problem

Abstract: The Monash University shooting which occurred in 2002, in Melbourne Australia, is analysed using claims-making theory and the four-stage natural history model of social problems. As Spector and Kitsuse argue, social problems ‘are what people think they are’ rather than objective problems. This incident – a shooting of two classmates by a mentally ill offender who suffered from persecutory delusions – was framed as a gun problem rather than a socially or psychologically related crime. In doing so, journalists m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Extant literature on the mediatisation of school shootings in general has focused on newsworthiness (Lawrence and Mueller, 2003; Schildkraut et al, 2018), the discourse of fear and moral panic (Altheide, 2009; Burns and Crawford, 2000; Kupchik and Bracy, 2009), and the ethical response of journalists (Blackholm et al, 2012). Many assess attribute-agenda setting and framing of stories in the media (Chyi and McCombs, 2004; Elsass et al, 2016; Kwon and Moon, 2009; Muschert and Carr, 2006; Peelo, 2006; Wondermaghen, 2013) but frame analysis is not the same as narrative analysis. While media frames refer to the mental schemes for presenting and comprehending news (Scheufele, 1999) narrative ritual analysis is concerned with the function of symbolism and storytelling devices journalists rely upon to make sense of the world (Kitch, 2003).…”
Section: Mass Shootings In the Newsmentioning
confidence: 99%
“…Extant literature on the mediatisation of school shootings in general has focused on newsworthiness (Lawrence and Mueller, 2003; Schildkraut et al, 2018), the discourse of fear and moral panic (Altheide, 2009; Burns and Crawford, 2000; Kupchik and Bracy, 2009), and the ethical response of journalists (Blackholm et al, 2012). Many assess attribute-agenda setting and framing of stories in the media (Chyi and McCombs, 2004; Elsass et al, 2016; Kwon and Moon, 2009; Muschert and Carr, 2006; Peelo, 2006; Wondermaghen, 2013) but frame analysis is not the same as narrative analysis. While media frames refer to the mental schemes for presenting and comprehending news (Scheufele, 1999) narrative ritual analysis is concerned with the function of symbolism and storytelling devices journalists rely upon to make sense of the world (Kitch, 2003).…”
Section: Mass Shootings In the Newsmentioning
confidence: 99%
“…This influence has also been referred to as media effects (Potter, 2012: 38). Wondemaghen (2014: 697) states that through framing, especially by including and excluding interpretations, the mass media have the power to direct audiences to those issues which are of concern and those which are not.…”
Section: Media Language and Framingmentioning
confidence: 99%
“…They found that the shootings were initially framed at the individual and community level, then framed based on implications for society, and, finally, the frame changed back to the community level (Muschert and Carr, 2006: 760). Wondemaghen (2014: 696), by contrast, demonstrated that school shootings, as reported in the media ‘. .…”
mentioning
confidence: 98%